2002
DOI: 10.2175/106143002x139712
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Biofiltration for Odor Control: Model Calibration, Validation, and Applications

Abstract: A dynamic model that describes the biofiltration process for hydrogen sulfide removal from wastewater treatment plant air emissions was calibrated and validated using pilot-and full-scale biofilter data obtained from the Cedar Rapids (Iowa) Water Pollution Control Facilities. After calibration, the model was found to predict the dynamic effluent concentrations of the pilot-and full-scale biofilters well, with the measured data falling within 58 to 80% of the model output values. In addition, the model predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…This result indicates that the additional nutrients and high water/toluene sorption capacity of the mixed packing materials facilitated the rapid recovery of the toluene degrading capacity. The same characteristics were noted by other authors [13,16,[37][38][39].…”
Section: Biotrickle Filtrations In Overload and Shutdown Periodssupporting
confidence: 88%
“…This result indicates that the additional nutrients and high water/toluene sorption capacity of the mixed packing materials facilitated the rapid recovery of the toluene degrading capacity. The same characteristics were noted by other authors [13,16,[37][38][39].…”
Section: Biotrickle Filtrations In Overload and Shutdown Periodssupporting
confidence: 88%
“…The uptake of hydrogen sulphide on the concrete surfaces was fast compared to release rates of hydrogen sulphide from wastewater [8]. This observation corresponds to the observations by Martin et al [11], who reported that residence times lower than 10 sec in a biofilter were sufficient for treating gas streams for 100 ppm hydrogen sulphide. () ( ) in the thickness of the layer of corrosion products both between the different reactors and between the individual concrete segments of each reactor.…”
Section: Gas Phase Removal Kineticssupporting
confidence: 84%
“…Recovery of the energy content in the form of methane is advantageous, as is recovery or removal of the sulfur if sulfide is formed (Khanal and Huang 2003;Martin et al 2002).…”
Section: Introductionmentioning
confidence: 99%